2011
DOI: 10.1136/gutjnl-2011-300608
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow transplantation improves hepatic fibrosis inAbcb4−/−mice via Th1 response and matrix metalloproteinase activity

Abstract: These results show that BM-Tx causes an antifibrotic Th1 response combined with transient inflammatory effects and subsequently upregulated MMP activity. Antifibrotic Th polarisation and prolonged proteolytic activity, especially of MMP-9, might be responsible for long-term amelioration of hepatic fibrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 74 publications
1
25
0
Order By: Relevance
“…In contrast, we found a significantly more pronounced increase in MMP-9 levels from baseline to 2-3 weeks in the mBMC group compared to controls. In accordance with our findings Roderfelt et al demonstrated a transient inflammatory response and upregulation of MMP-9 activity after bone marrow transplantation in Abcb 4 −/− (hepatic fibrosis) mice [26]. We have previously shown that MMP-9 levels are reduced 1 day after AMI [27].…”
Section: Discussionsupporting
confidence: 92%
“…In contrast, we found a significantly more pronounced increase in MMP-9 levels from baseline to 2-3 weeks in the mBMC group compared to controls. In accordance with our findings Roderfelt et al demonstrated a transient inflammatory response and upregulation of MMP-9 activity after bone marrow transplantation in Abcb 4 −/− (hepatic fibrosis) mice [26]. We have previously shown that MMP-9 levels are reduced 1 day after AMI [27].…”
Section: Discussionsupporting
confidence: 92%
“…Thus, it is considered feasible to directly transfuse fresh bone marrow (bone marrow transplantation (BMT)) to achieve therapeutic goals. 6, 7 To assess the efficacy and safety of transfusing autologous bone marrow in AIDS patients accompanied by advanced liver cirrhosis, we conducted a single-arm trial. The protocol was approved by the Ethics Committee of the Public Health Clinical Center Affiliated with Fudan University.…”
mentioning
confidence: 99%
“…The anti-fibrotic effect of BM-derived stem cells has been reported to be accompanied by significant upregulation of matrix metalloproteinases in the injured liver, predominantly MMP-9 but also MMP-2 and -13 [39,44,50]. This has been observed following infusions of both HSC and MSC, and reported to persist for up to 20 weeks following cell infusion [50].…”
Section: Mechanisms Of Actionmentioning
confidence: 85%
“…This has been observed following infusions of both HSC and MSC, and reported to persist for up to 20 weeks following cell infusion [50]. Although increased MMP expression may mediate the anti-fibrotic effect, the cellular source remains unclear.…”
Section: Mechanisms Of Actionmentioning
confidence: 99%